La comunicación visual a través del arte (El placer del reconocimiento) - Fernández Polanco, Aurora (Anuario del Departamento de Historia y Teoría del Arte, 1992)
The images of our everyday visual culture are tainted by an "artiness", full of allusions and borrowings of "visual quotations" from High culture. This means that we frequently experience a "pleasure in recognition" not that of reality in a painting, but rather of a painting in reality. These days, when a good deal of reality consists of images and when artists have noticeably enriched our "visual heritage" we should ask ourselves, from our "chronic habit of contemplation", what the nature of our sight is, and what the new ways of seeing are. We should point out the importance of "dejá vu" in the language of publicity, knowing that it is a contaminated and contaminating discourse.